Pregnancy-Associated Plasma Protein-A: Its Significance as a Single Biomarker for Adverse Obstetric Outcomes - Dey, Madhusudan; Choudhury, Priyanshi; Chawla, Sunil; Dhume, Pranjali; Goel, Suyash; Shah, Ankur; Gowda KN, Mounica (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVES: Low levels of pregnancy-associated plasma protein-A in pregnant women linked to unhealthy placentation and a spectrum of maternal and fetal complications. Its assessment as a single biomarker has the potential to identify high-risk pregnancies. This prospective observational study was conducted to find a correlation between low pregnancy-associated plasma protein-A levels in the first trimester of pregnancy with various obstetric outcomes to establish if it can be used as a single biomarker for counseling couples. STUDY DESIGN: The study was conducted at Base Hospital, Delhi Cantt. Maternal serum pregnancy-associated plasma protein-A levels were assessed at 11 to 13+6 weeks of gestation, converted in multiples of the median and patients were followed till delivery. Maternal outcomes were recorded in terms of abortions, development of gestational hypertension, gestational diabetes, preeclampsia, placental abruption, fetal growth restriction, fetal demise, neonatal intensive care unit admission, etc., and analyzed to find an association with levels first trimester of pregnancy-associated plasma protein-A. RESULTS: Low pregnancy-associated plasma protein-A levels showed a statistically significant association with gestational hypertension, preeclampsia, abortion, fetal demise, and also for adverse neonatal outcomes like APGAR <5 at 1 min, fetal growth restriction, neonatal intensive care unit admission, and perinatal deaths. No significant association was observed for preterm delivery, gestational diabetes, and placental abruption. CONCLUSION: Serum pregnancy-associated plasma protein-A levels in the first trimester of pregnancy have the potential of being utilized as a validated marker for adverse pregnancy outcomes. Early identification of such pregnancies can help in optimizing feto-maternal outcomes through closer surveillance, timely intervention, and referral to tertiary care centers. Further research would help the fraternity in developing a prediction model.